Challenges and Opportunities in Reading Instruction for Children with Limited Speech - Barton-Hulsey, Andrea (Seminars in Speech and Language, 2017)
The ability to read has implications for communication development for individuals who use augmentative and alternative communication (AAC) systems. Access to print for generative language provides a flexible system in which an individual can create novel messages and interact with his or her family, friends, and peers. Several challenges in reading instruction inherently exist for individuals who have limitations in speech ability. Reading instruction is becoming increasingly more accessible with current advances in technology; however, several challenges remain regarding the creation of accessible learning environments, assessment tools, and reading intervention strategies for children with limited speech. The current article provides an overview of the role of the speech-language pathologist in reading instruction and particularly addresses children's need for more experience with instruction in phonological awareness and decoding, an area that has presented the greatest challenge in access to reading instruction for individuals who use AAC. Several considerations are presented to increase access to instruction with directions for future research highlighted.
Keywords: Augmentative and alternative communication; intellectual and developmental disability; phonological awareness; reading; decoding